A DSM-Based CCPM-MPL Representation Method for Project Scheduling under Rework Scenarios - Guofeng Ma; Ming Wu; Keke Hao; Shanshan Shang (Advances in Civil Engineering)
Rework risks caused by information flow interactions have become a major challenge in project scheduling. To deal with this challenge, we propose a model integrating the critical chain project management method, design structure matrix method, and max-plus method. Our model uses a start-to-start relationship of activities instead of the traditional finish-to-start relationship, which also allows overlaps between activities. We improve the accuracy of the rework safety time in two ways: (1) the overall overlapping effect is taken into consideration when calculating the rework time of an activity arising from the information flow interaction of its multiple predecessors overlapped with it; (2) the rework time arising from activity overlaps, the first rework time, and the second rework time are calculated as components of the rework safety time in our model, while the last one is ignored in traditional methods. Furthermore, the accuracy of time buffers is improved based on the improved rework safety time. Finally, we design the max-plus method to generate project schedules and appropriately sized time buffers. The empirical results show that the project schedule generated by the proposed method has a higher on-time completion probability, as well as more appropriately sized project buffers.